The Effect of Different Types of Essential Oils on Some Blood Characteristics of Awassi Lambs - Bashar Adham Ahmed; Ayser Hamid Salman; Osama Hamid Shehab; Ahmed Sinan Ahmed (The Indian Veterinary Journal, 2024)
This study was conducted in the fields of the College of Veterinary Medicine - Tikrit University. The study included 20 Awassi lambs, 5 lambs for each treatment (T1 control, T2 using laurel oil, T3 using clove oil, T4 using sage oil) at the age of 6 months, dosed daily with a concentration of 500 mg/animal of the mentioned oils for a period of 90 days. This study is aimed to evaluate the effect of essential oils on blood characteristics (total protein, albumin, glucose, urea, cholesterol, triglycerides, uric acid, creatinine, calcium, magnesium, GOT, GPT, HDL, VDL, LDL, ALP).The results showed that using sage and clove oil was superior to the control treatment in terms of glucose (82.40, 80.40, 67.20, 56.80mg/dl)and triglycerides (91.40, 63.40, 60.20, 59.60 mg/dl), and adding clove oil was superior to the control treatment in calcium (9.81, 9.20, 9.32, 8.32 mg/dl) and magnesium (5.62, 5.40, 4.66, 4.56 mg/dl) and GPT (28.60, 24.80, 22.0, 21.80 U/L) and HDL (29.60, 26.60, 25. 40, 24.20 mg/dl). The laurel oilusing treatment was superior to the control in VDL (17.60, 16.20, 16.0, 14.80 mg/dl).